Differences between preschool children using tablets and non-tablets in visual perception and fine motor skills - Ling-Yi Lin (SAGE Publishing, 2019)
Background Numerous touch-screen applications designed to support visual perceptual skills and fine motor development for young children are available. Objectives This study aimed to investigate whether or not there were differences between children using tablets and non-tablets in visual perception and fine motor skills and to examine the association between visual perception and fine motor skills in two groups. Methods This study had tablet and non-tablet groups, each with 36 typically developing preschool children. Results Children in the non-tablet group yielded significantly higher scores in the subtests of visual discrimination, visual memory, spatial relationships, form constancy, visual figure ground, fine motor precision, fine motor integration, and manual dexterity than those in the tablet group. The association between visual perception and fine motor skills demonstrated different patterns in the two groups. Conclusion There are differences in visual perception and fine motor skills between children using tablets and non-using tablets. Different patterns of association relationship support the need for occupational therapists to consider the underlying mechanism.